The impact of CO2 taxation on Swiss households' heating demand - Laurent Ott; Sylvain Weber (University of Neuchâtel, Institute of Economic Research (IRENE), 2018)
This paper investigates the impacts of the Swiss CO2 levy on households' heating demand. Using a difference-in-differences approach combined with inverse probability of treatment weighting, we test whether the 2016 carbon tax rate increase had a short-term impact on Swiss households' heating consumption and propensity to renovate. Micro-level data from the 2016 and 2017 waves of the Swiss Household Energy Demand Survey (SHEDS) are used to estimate the models. In both cases, no statistically significant effect can be detected across a variety of specifications. Even though further research is needed to investigate possible long-run impacts, our findings question the relevance of this policy instrument under its current form to lower households' greenhouse gas emissions. Additional measures might be implemented to improve its efficiency.
Keywords: C21; C23; H23; Q41; Q58; 330; Carbon tax; energy consumption; fossil fuel; policy evaluation; inverse probability of treatment weighting; difference-in-differences